Philosophie des HipHop Performen, was an der Zeit ist - Manemann, Jürgen (X-Texte zu Kultur und Gesellschaft, 2018)
Philosophers and rappers jointly explore in discussions, texts, songs, comments and spontaneous associations what philosophy of hip-hop means, the focus being on living philosophyzing. Philosophyzing in the sense of hip-hop requires getting personally involved. What is dreaded is not amateurism but copying the thoughts of others. In the confrontation with the thoughts of others, your own thoughts flash through your head. Authenticity, respectively realness and creativity: These are the ethical values of hip-hop. The philosophy of hip-hop does not mean talking philosophy but doing philosophy - namely when facing the challenges of modern life. The philosophy of hip-hop means performing what's happening.